2022
DOI: 10.1038/s42003-022-03148-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron and manganese co-limit the growth of two phytoplankton groups dominant at two locations of the Drake Passage

Abstract: While it has been recently demonstrated that both iron (Fe) and manganese (Mn) control Southern Ocean (SO) plankton biomass, how in particular Mn governs phytoplankton species composition remains yet unclear. This study, for the first time, highlights the importance of Mn next to Fe for growth of two key SO phytoplankton groups at two locations in the Drake Passage (West and East). Even though the bulk parameter chlorophyll a indicated Fe availability as main driver of both phytoplankton assemblages, the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…This indirect effect can be accounted for by defining a state of “Mn deficiency,” which instead normalizes Q Mn to the amount of Mn required to support growth rates in the absence of Fe limitation (i.e., Q Mn,Req,max ). Conceptually, our definition of Mn deficiency is similar to the additive responses observed in bottle incubations where simultaneous addition of both Mn and Fe increase biomass more than addition of Fe alone (Balaguer et al., 2022 ; Browning et al., 2021 ). In the standard version of the model, over half of the Southern Ocean experiences “Mn deficiency” at some point during the seasonal cycle (62% of waters poleward of 40°S; Figure 3f ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This indirect effect can be accounted for by defining a state of “Mn deficiency,” which instead normalizes Q Mn to the amount of Mn required to support growth rates in the absence of Fe limitation (i.e., Q Mn,Req,max ). Conceptually, our definition of Mn deficiency is similar to the additive responses observed in bottle incubations where simultaneous addition of both Mn and Fe increase biomass more than addition of Fe alone (Balaguer et al., 2022 ; Browning et al., 2021 ). In the standard version of the model, over half of the Southern Ocean experiences “Mn deficiency” at some point during the seasonal cycle (62% of waters poleward of 40°S; Figure 3f ).…”
Section: Resultsmentioning
confidence: 90%
“…Relative to other Fe-limited regions where Mn supply is greater (e.g., the Subarctic Pacific), the first reports of dMn in the Southern Ocean emphasized unusually low concentrations, proposing the potential for Mn co-limitation alongside Fe . More recent surveys have confirmed that dMn in both the Antarctic and Subantarctic zones can be <0.05 nM, the lowest measured globally, especially in remote waters away from continental margin and islands (Balaguer et al, 2022;Browning et al, 2014;Latour et al, 2021;Middag et al, 2011Middag et al, , 2013. Surface waters south of the Polar Front also feature Zn 2+ concentrations that are 100-1,000-fold higher than temperate and tropical regions, which should depress algal Mn uptake via competition for membrane transporters (Baars & Croot, 2011;Baars et al, 2014).…”
mentioning
confidence: 99%
“…Experimental work using nutrient additions has shown that the phytoplankton community in the Southern Ocean can also respond to addition of volcanic ash (containing both Mn and Fe) [ 22 ]. Co-limitation between Mn and Fe has been detected in Drake Passage, both in the western [ 23 ] and central part [ 7 ] of the passage, and in McMurdo Sound in the Ross Sea [ 8 ]. Additionally, the species Chaetoceros debilis has been shown to be Mn deficient in the Atlantic sector of the Southern Ocean [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other micronutrients beyond iron, predominantly manganese, have been shown to play an important role in controlling oxidative stress by catalysing antioxidant production in some diatom species (McCain et al, 2021), explaining the observed phenomena of iron-manganese co-limitation in the Southern Ocean (Browning et al, 2021, Pausch et al, 2019, Balaguer et al, 2022. Despite the importance of micronutrients such as manganese in controlling phytoplankton growth, particularly during seasonal transitions (Browning et al, 2021)…”
Section: Micronutrient Supply and Uptakementioning
confidence: 99%